2017
DOI: 10.1111/bjd.14935
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced photosensitivity: new insights into pathomechanisms and clinical variation through basic and applied science

Abstract: Drug-induced photosensitivity occurs when a drug is capable of absorbing radiation from the sun (usually ultraviolet A) leading to chemical reactions that cause cellular damage (phototoxicity) or, more rarely, form photoallergens (photoallergy). The manifestation varies considerably in presentation and severity from mild pain to severe blistering. Despite screening strategies and guidelines in place to predict photoreactive drugs during development there are still new drugs coming onto the market that cause ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 93 publications
0
60
0
7
Order By: Relevance
“…Our photobiological explorations showed that UVA irradiation influenced PFD photosensitivity, as in most drug-induced photosensitization. 8 Very few cases with PFD phototesting have been reported. 3,6 In one case, UVA and UVB MEDs were decreased.…”
mentioning
confidence: 99%
“…Our photobiological explorations showed that UVA irradiation influenced PFD photosensitivity, as in most drug-induced photosensitization. 8 Very few cases with PFD phototesting have been reported. 3,6 In one case, UVA and UVB MEDs were decreased.…”
mentioning
confidence: 99%
“…Although drug‐induced photosensitivity is considered to account for up to 8% of reported cutaneous adverse events from drugs, reliable data on its actual incidence are lacking so far. It is generally assumed that drug‐induced photosensitivity is heavily underreported owing to a lack of clinical recognition and a lack of reporting to databases . This most probably results in an appreciable number of underdiagnosed and underreported cases hampering retrospective analyses of the true incidence of drug‐induced photosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The action spectrum mostly lies within the UVA range although some drugs are activated by visible light or UVB radiation or a combination of different wavelengths. 2 The mechanisms for tissue damage in phototoxicity involve oxidation of cellular lipids, proteins and DNA, often mediated by reactive oxygen species (ROS), 3,4 or formation of stable photoadducts. 5 Photoallergy represents a Tcell-mediated delayed-type hypersensitivity reaction that involves covalent binding of a pharmaceutical compound to an endogenous protein in the presence of solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 300 drugs are reported to be photosensitizers, with new ones added every year. However, the incidence of drug‐induced photosensitivity is low. Several classes of antihypertensive drugs are also described as being photosensitizing . However, the mechanism of action is poorly understood.…”
Section: Introductionmentioning
confidence: 99%